Implementasi Metode Rapid Application Development Pada Pengembangan Perpustakaan Digital Web di Rumah Sakit Jiwa Atma Husada Mahakam - Akbar Bintang Wicaksono; Sayekti Harits Suryawan (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
The pivotal role of digital libraries in facilitating access to resources and supporting learning and research is indisputable. At Atma Husada Mahakam Mental Hospital, a digital library becomes imperative for bolstering scientific resource availability and streamlining information management. This research advocates for a web-based digital library system employing the Rapid Application Development (RAD) method, utilizing Laravel 10 technology, and MySQL as the database. This approach facilitates a concise, swift, and iterative development process. Data, gathered through observation, interviews, and literature reviews, inform the stages of requirement planning, user design, construction, and cutover, with Black Box Testing employed for testing. The resultant digital library system minimizes time, space, and enhances staff effectiveness, promoting paper usage efficiency and improved book accessibility. The implementation at Atma Husada Mahakam Mental Hospital anticipates creating an informative, modern, and efficient environment fostering psychology and research development.